P23-Specific IgY significantly reduces diarrhea and oocyst shedding in calves experimentally infected with Cryptosporidium parvum - Mira, Anabela; Garro, Carlos Javier; De Alba, Paloma; Monti, Demián Esteban; Lang, Maria Cecilia; Vivas, Alejandro; Medina, Esteban; Franco, Juan Cruz; Gutierrez, Álvaro; Schnittger, Leonhard; Wigdorovitz, Andres; Parreño, Gladys Viviana; et al. (MDPI, 2025)
Background/Objectives: Cryptosporidium parvum is a zoonotic enteroparasite causing severe diarrhea in newborn calves, leading to significant economic losses in dairy and beef farming. This study aimed to evaluate whether C. parvum p23-specific IgY antibodies could control neonatal calf diarrhea caused by C. parvum. Methods: A recombinant immunogen comprising the p23 protein fused to the antigen-presenting cell homing (APCH) molecule was expressed using the baculovirus system. Hens were immunized with the APCH-p23 immunogen, and the resulting IgY was spray-dried for treatment use. Eight newborn calves were included in the study and received commercial colostrum within the first 12 h of life. Four calves were treated with 20 g of powdered egg containing IgY (p23-specific IgY titer of 256 in milk) twice daily for 7 days. The remaining four calves received regular non-supplemented milk. All calves were orally infected with 6 million oocysts and monitored for 21 days. Results: Calves treated with p23-specific IgY exhibited significantly reduced diarrhea duration (3.5 vs. 7.5 days; p = 0.0397) and oocyst shedding duration (6.50 vs. 12 days; p = 0.0089). In addition, the total number of excreted oocysts, as measured by the change of the area under the curve (AUC), was significantly reduced in the treated group (14.25 vs. 33.45; p = 0.0117). Although the onset of diarrhea was delayed (3.5 to 6.5 days post-infection; p = 0.1840), and diarrhea severity was reduced (24.25 to 17 AUC; p = 0.1236), both parameters were not statistically significant. Conclusions: P23-specific IgY antibodies effectively reduced the C. parvum-induced duration of diarrhea in experimentally infected calves. These findings highlight the potential of this passive treatment as a promising strategy for controlling neonatal calf diarrhea.